Foliar anatomy of the subfamily Myrtoideae (Myrtaceae) - Cardoso, C. M. V. [UNESP]; Proenca, S. L. [UNESP]; Sajo, M. G. [UNESP] (CSIRO Publishing, 2009)
The foliar structure of 44 species of Myrtoideae Nied. (Myrtaceae) was described to characterise the anatomy of the leaves in this subfamily and also to recognise particular features in each genus and/or subtribe. In the present study, nine genera of the subtribe Myrtinae, five genera of the subtribe Myrciinae and eight genera of the subtribe Eugeniinae were examined. All of them have dorsiventral and hypostomatic leaves, with stomata slightly protruded in relation to other epidermal cells; the leaves also present secretory cavities, idioblasts containing druses and vascular bundles with phloem on both adaxial and abaxial sides. Some surface features have diagnostic value for all genera of these three subtribes, such as the percentage of palisade parenchyma, the presence or absence of an adaxial hypodermis, the occurrence of an extension to the vascular bundle sheath, and the shape and position of the vascular system of the midrib. These features are described for each of the species studied and the results are discussed in a taxonomical context.